Serving the Public Interest in Several Ways: Theory and Empirics - Robert Dur; Max van Lent (Center for Economic Studies and ifo Institute (CESifo), 2017)
We develop a model where people differ in their altruistic preferences and can serve the public interest in two ways: by making donations to charity and by taking a public service job and exerting effort on the job. Our theory predicts that people who are more altruistic are more likely to take a public service job and, for a given job, make higher donations to charity. Comparing equally altruistic workers, those with a regular job make higher donations to charity than those with a public service job by a simple substitution argument. We subsequently test these predictions using the German Socio-Economic Panel Study, which contains data on self-reported altruism, sector of employment, and donations to charity for more than 7,500 workers. We find support for most of our predictions.
Keywords: D64; H11; J45; M50; 330; altruism; charitable donations; public service motivation; public sector employment; self-selection